On the periodicity of inventories - Katsuyuki Shibayama (University of Kent, Department of Economics, 2008)
This article studies inventories and monetary policy by estimating VAR models. The complex roots detected in our estimation generate cycles of around 55 to 70 months, which are quite close to actual business cycle lengths. This implies that production and inventories follow damped oscillations (stable sine curves), implying that a boom is the seed of the following recession, and vice versa. Interestingly, the peaks and troughs of policy interest rate precedes those of production in the U.S. (i.e., forward-looking monetary policy), but not in Japan. The central banks in both countries react sharply to demand shocks, but not to supply shocks, because booms after positive demand shocks last longer as firms replenish reduced inventories, while booms after positive supply shocks are short-lived as the initial accumulation of inventories suppresses production in subsequent periods.
Keywords: E32; E58; C32; 330; inventories; inventory cycle; business cycle; monetary policy; damped oscillations; phase shift; spectrum; Konjunktur; Lagerzyklus; Produktion; Geldpolitik; VAR-Modell; USA; Japan